Some stock farm equipments - Morlan, Fred Byers (My University, 1900)
Introduction: Many farmers who are engaged in the live stock industry are sadly hampered by a lack of conveniences, or even those things almost essential to successful work. Much of this is due more to an ignorance of what is really required and may be obtained than from financial difficulties. While it is true that some of these inconveniences were due to a lack of means necessary for a proper equipment at the start, much of it can be explained by the disadvantage under which the early settlers of the western state labored in regard to the existing conditions, and the lack of experience as to how best to meet them. Others have failed to keep posted on the many modern contrivances which have been invented and introduced, or the constant advance, in this age of progress, of new and improved methods. The farmer’s work may often be greatly lightened and better results secured by the intelligent use and application of methods, principles and machines, familiar to some, but comparatively new to others. Some persons have little use for certain things which others consider almost indispensable, perhaps through ignorance of their real value, or an actual knowledge of their worthlessness. It is the purpose of this paper to discuss certain methods and contrivances, and also offer others, which, in the writer’s opinion, are superior to many in common use.
Citation: Morlan, Fred Byers. Some stock farm equipments. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Agriculture; Livestock Farming; Farming Equipment; Stock Farms; Theses